2013
DOI: 10.1210/me.2012-1357
|View full text |Cite
|
Sign up to set email alerts
|

miR-449a Contributes to Glucocorticoid-Induced CRF-R1 Downregulation in the Pituitary During Stress

Abstract: The hypothalamic-pituitary-adrenal axis is controlled by the feedback of glucocorticoids on the hypothalamus and pituitary. Stress increases CRF, ACTH, and glucocorticoid secretion. The expression of not only CRF mRNA in the hypothalamus and proopiomelanocortin mRNA in corticotrophs, but also CRF type 1 receptor (CRF-R1) mRNA and protein on corticotrophs are downregulated through glucocorticoids. However, the mechanisms underlying the glucocorticoid-induced CRF-R1 downregulation are not fully understood. Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
4
24
0
2
Order By: Relevance
“…The expression of miR449a in the anterior pituitary was increased by restraint in NBW offspring but not in LBW offspring. We have previously demonstrated that overexpression of miR449a suppressed mRNA and protein expression of Crhr1, and knockdown of miR449a blocked dexamethasone-induced suppression of Crhr1 expression (Nemoto et al 2013), indicating that miR449a suppresses Crhr1 expression. Results of a previous in vitro study had also indicated that the expression of miR449a was positively regulated by glucocorticoids, but not by CRF.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The expression of miR449a in the anterior pituitary was increased by restraint in NBW offspring but not in LBW offspring. We have previously demonstrated that overexpression of miR449a suppressed mRNA and protein expression of Crhr1, and knockdown of miR449a blocked dexamethasone-induced suppression of Crhr1 expression (Nemoto et al 2013), indicating that miR449a suppresses Crhr1 expression. Results of a previous in vitro study had also indicated that the expression of miR449a was positively regulated by glucocorticoids, but not by CRF.…”
Section: Discussionmentioning
confidence: 92%
“…SDS sample buffer (200 mM Tris-HCl, pH 6.8, 30% glycerol, 6% SDS, 0.03% bromophenol blue, and 3% b-mercaptoethanol) and boiled for 5 min. They were then separated by SDS-PAGE and transferred onto (Nemoto et al 2013). Membranes were washed and incubated with HRP-conjugated antigoat IgG (Jackson Immuno Research Laboratory, West Grove, PA, USA).…”
Section: Western Blotting Of Crhr1mentioning
confidence: 99%
See 2 more Smart Citations
“…Egy másik tanulmány-ban az egér központi idegrendszerének különböző részeit vizsgálva sikerült agyalapimirigyre specifikus miRNS-eket azonosítani [22]. Amellett, hogy a miRNSeknek az emberben is fontos szerepük van a normál mirigy fejlődésében [19,23,24] és hormontermelésében [25][26][27][28][29][30][31], az elmúlt években egyre több humán vizsgálat támasztja alá azt is, hogy részt vehetnek az adenomák kialakulásában és növekedésében [32][33][34][35].…”
Section: Mirns-expressziós Eltérések Az Agyalapimirigy-daganatokbanunclassified